Workforce Management Decisions in the Construction Industry in the UAE - Nayeem, Mohammed Abdul (Journal of Comparative International Management, 2020)
This study is guided by the need to develop a framework for workforce management decisions in the context of the construction industry in the UAE. A full contextual framework involving all the factors that can possibly play a role in the success of workforce management decisions has been delineated. The factors considered are related to hiring, selection, and quality of workers. The literature has focused not only on the overarching strategies and tactics but also on how day-to-day decision-making occurs while using human resource management for productivity growth of an organization. The data was collected from three construction companies in the UAE. The findings of the study are in line with the findings of previous works.